PENGARUH BUDAYA ORGANISASI DAN LOYALITAS KERJATERHADAP KINERJA PEGAWAI PT PLN (PERSERO) UNITINDUK PEMBANGKITAN SUMATERA BAGIAN SELATAN - Muhammad Hairul; Muhammad Ridwan; Nina Fitriana (JURNAL KOMPETITIF, 2020)
The purpose of this study was to determine the influence of Organizational Culture  and Job Loyalty  as independent variables to be examined for their effects on employee performance either jointly or simultaneously or partially. After conducting a literature review and hypotheses, data was obtained from the distribution of questionnaires for 60 employees of PT PLN (Persero) South Sumatra Main Generation Unit, and then analyzed the data obtained using quantitative data analysis.The results of this study showed that the influence of Organizational Culture  and Job Loyalty  simultaneously obtained a significant value of F of 0.000 which is smaller than α of 0.05 (0.000 <0.05) so that Ho is rejected and H1 is accepted, meaning that there is an influence. significantly between Organizational Culture  and Job Loyalty  together on Employee Performance at PT PLN (Persero) South Sumatra Generation Main Unit. The partial test for the Organizational Culture variable obtained a significant t value of 0.000 which is smaller than α of 0.05 (0.000 <0.05) meaning that partially Organizational Culture  has an effect on Employee Performance and the results of the Work Loyalty variable) has a significant value of 0.000 which is smaller than α of 0.05 (0.000 <0.05) which means that partially there is a significant influence between commitment to employee performance.Keywords :Employee Performance, Organizational Culture and Work Loyalty.